Sirolimus-eluting coronary stents in octogenarians: a 1-year analysis of the worldwide e-SELECT Registry. - Hong, Y; Jeong, M; Abizaid, A; Banning, A; Bartorelli, A; Dzavik, V; Ellis, S; Gao, R; Holmes, DR; Legrand, V; Neumann, F; Spaulding, C; et al. (2011)
OBJECTIVES: The aim of this study was to identify the worldwide practice of Cypher Select (Cordis Corporation, Bridgewater, New Jersey) or Cypher Select Plus sirolimus-eluting stent (SES) in patients 80 years of age (octogenarian) and to identify clinical outcomes in this patient population. BACKGROUND: The use of drug-eluting stents in elderly patients may have different features compared with younger patients. METHODS: Between 2006 and 2008, 15,147 patients from 320 hospitals in 56 countries were enrolled in a registry. Initial implantation and follow-up outcome information obtained at 1-year follow-up in 675 octogenarian patients were compared with those in 14,472 nonoctogenarian patients. RESULTS: Octogenarians had significantly more comorbidities and had higher Charlson comorbidity index scores (1.5 ± 1.6 vs. 1.0 ± 1.3, p < 0.001). Rates of cardiac death (3.3% vs. 0.9%, p < 0.001), myocardial infarction (2.3% vs. 1.9%, p = 0.021), and definite or probable stent thrombosis (2.3% vs. 0.9%, p = 0.0002), and major bleeding (2.0% vs. 0.9%, p = 0.015) were significantly higher in octogenarians at 1 year; however, there was no significant difference in the rate of target lesion revascularization between the 2 groups (3.2% vs. 2.2%, p = 0.12). In octogenarians, a high Charlson comorbidity index was an independent predictor of death and stent thrombosis up to 360 days from the index procedure (hazard ratio: 1.3, 95% confidence interval: 1.1 to 1.5, p < 0.001, and hazard ratio: 1.5, 95% confidence interval: 1.3 to 1.8, p < 0.001, respectively). CONCLUSIONS: Stenting with SES may be an effective therapeutic option in elderly patients, with acceptable rates of complications and a very low rate of repeat revascularization as demonstrated by this e-SELECT (A Multi-Center Post-Market Surveillance Registry) subgroup analysis.